2018
DOI: 10.6063/motricidade.14914
|View full text |Cite
|
Sign up to set email alerts
|

Body-image and -size perception after a single session of HIIT body work in healthy adult men

Abstract: It was our objective to analyze the effects of a single session of whole body HIIT on body-image and -scheme parameters of healthy adult men. Twenty-one active, healthy adults performed high-intensity intermittent training based on full body exercise. The training session involved 20 sets of 30 second all-out exercise and 30 seconds of passive recovery between sets. All subjects underwent blood lactate measurement, rate of perceived exertion, feeling scale and body image assessment and perception of body size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Our data indicated that both sessions corresponded to 89% of maximum HR and 11 to 12mmol.L -1 of lactate, values similar to other studies for both HR and lactate concentration that used HIIT with body weight. 10,25,31 The mean values of RPE in the present study are also in agreement with the data available in the literature with HIIT using body weight 31,33 , Additionally, considering the perception of pleasure, there was no difference between both exercise conditions. So, it is possible to consider that the addition of electrical stimulation does not influence this indicator.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data indicated that both sessions corresponded to 89% of maximum HR and 11 to 12mmol.L -1 of lactate, values similar to other studies for both HR and lactate concentration that used HIIT with body weight. 10,25,31 The mean values of RPE in the present study are also in agreement with the data available in the literature with HIIT using body weight 31,33 , Additionally, considering the perception of pleasure, there was no difference between both exercise conditions. So, it is possible to consider that the addition of electrical stimulation does not influence this indicator.…”
Section: Discussionsupporting
confidence: 91%
“…It is worth mentioning that studies 24,30 indicate that exercises with values above 6 METS are considered to be intense. Other intensity indicators popularly used in high-intensity exercise sessions using body weight are HR 10,22 and lactate concentration 10,31 . Our data indicated that both sessions corresponded to 89% of maximum HR and 11 to 12mmol.L -1 of lactate, values similar to other studies for both HR and lactate concentration that used HIIT with body weight.…”
Section: Discussionmentioning
confidence: 99%
“…The first drop of blood was discarded, and free flow blood was collected in glass capillary tubes. All blood samples used for lactate analysis were evaluated using an Accutrend® (Roche—Basel, Switzerland) as described previously ( Machado et al, 2018a ; Rica et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Subjects reported their rating of perceived exertion (RPE, scale 1–10) as described by Borg (0–10) ( Foster et al, 2017 ), immediately at the end, and prior to each exercise set as previously outlined ( Machado et al, 2018a ; Machado et al, 2018b ; Rica et al, 2018 ). Recovery was measured using a scale adapted by Laurent et al (2011) and has been used previously in exercise studies ( Machado et al, 2018a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation